Biocompatibility and Anti-Microbiological Activity Characterization of Novel Coatings for Dental Implants: A Primer for Non-Biologists - Monsees, Thomas K. (Frontiers in Materials, 2016)
With regard to biocompatibility, the cardinal requirement for dental implants and other medical devices that are in long-term contact with tissue is that the material does not cause any adverse effect to the patient. To warrant stability and function of the implant, proper osseointegration is a further prerequisite. Cells interact with the implant surface as the interface between bulk material and biological tissue. Whereas structuring, deposition of a thin film or other modifications of the surface are crucial parameters in determining favorable adhesion of cells, corrosion of metal surfaces and release of ions can affect cell viability. Both parameters are usually tested using in vitro cytotoxicity and adhesion assays with bone or fibroblasts cells. For bioactive surface modifications, further tests should be considered for biocompatibility evaluation. Depending on the type of modification, this may include analysis of specific cell functions or the determination of antimicrobial activities. The latter is of special importance as bacteria and yeast present in the oral cavity can be introduced during the implantation process and this may lead to chronic infections and implant failure. An antimicrobial coating of the implant is a way to avoid that. This review describes the essential biocompatibility assays for evaluation of new implant materials required by ISO 10993 and also gives an overview on recent test methods for specific coatings of dental implants.